2022
DOI: 10.21203/rs.3.rs-1010519/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the Impact of COVID-19 Pandemic on The Physicians’ Psychological Health; A Scoping Systematic Review

Abstract: Background COVID-19 has endangered healthcare systems at multiple levels worldwide. Published data suggests that moral dilemmas faced during these unprecedented times have placed physicians at the intersections of ethical and unethical considerations. This phenomenon has questioned the physicians' morality and how that has affected their conduct. Our review taps into the spectrum of the transforming optics of patient care during the pandemic and its impact on psychological wellbeing.Methods We adopted the Ark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Studies also reported that community-level challenges and needs included mostly stigma and discrimination from society while expressing a need for support from community members. Societal stigmatization of HCWs during COVID-19 is not surprising as previous research [2,5,9,15] suggests that since the beginning of the COVID-19 pandemic, social prejudice and stigmatization was directed to HCWs as they were exposed to COVID-19 and community members feared that they would contract them COVID-19. Possible interventions at the community-based level might include educational campaigns on the measures required to control the spread of the virus.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Studies also reported that community-level challenges and needs included mostly stigma and discrimination from society while expressing a need for support from community members. Societal stigmatization of HCWs during COVID-19 is not surprising as previous research [2,5,9,15] suggests that since the beginning of the COVID-19 pandemic, social prejudice and stigmatization was directed to HCWs as they were exposed to COVID-19 and community members feared that they would contract them COVID-19. Possible interventions at the community-based level might include educational campaigns on the measures required to control the spread of the virus.…”
Section: Discussionmentioning
confidence: 84%
“…On March 11, 2020, coronavirus disease (COVID- 19) was declared by the World Health Organization [1] as a global pandemic and posed an extremely high risk, burden and negative impact on the physical and mental health especially of those frontline healthcare workers (HCWs) [1][2][3][4]. Healthcare systems in many countries at the time of the COVID-19 pandemic were on a brink of collapse, with HCWs exposed to unprecedented psychological strain [5] and experiencing an increased risk for infection and adverse physical health outcomes [3,4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent research has shown that social support and affective well-being are highly in uenced by emotional intelligence (45). In this context, development of faculty enhancement programs (46), seminars and forums for employees well-being and satisfaction (47), support services for academia and physicians by team leaders (48), and interprofessional collaboration (49) are considered to be effective in alleviating work-place based stress.…”
Section: Discussionmentioning
confidence: 99%